Asia Pacific fusion Japan's role in APEC - Funabashi, Yōichi 1944- (Inst. for Internat. Economics, 1995)
Released just before the Osaka summit hosted by Japan, this book looks closely at Japan's interests in APEC and its relations with countries in the region. It will provide an intellectual framework for discussion at Osaka and beyond of Japan's role in APEC
Keywords: Coopération économique Asie-Pacifique; Asia-Pacific Economic Cooperation; Economische betrekkingen; Außenwirtschaftspolitik; Asie - Relations économiques extérieures - Japon; Japon - Relations économiques extérieures - Asie; Japon - Relations économiques extérieures - Pacifique (région); Pacifique (région) - Intégration économique; Pacifique (région) - Relations économiques extérieures - Japon; Asien; Pazifischer Raum; Asia -- Foreign economic relations -- Japan; Japan -- Foreign economic relations -- Asia; Japan -- Foreign economic relations -- Pacific Area; Pacific Area -- Foreign economic relations -- Japan; Japan